Respon Pertumbuhan Bibit Lada (Piper ningrum Linn) Pada Pemberian Beberapa Dosis Pupuk Organik Cair (POC) Bonggol Pisang - Madani, Rona Tri; Sevindrajuta, Sevindrajuta; Sabri, Yunita; Akbar, Yustitia (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2024)
Research in the form of a field experiment on "Growth Response of Pepper Seedlings (Piper ningrum Linn) on Giving Several Doses of Liquid Organic Fertilizer (POC) Banana Weevil" has been carried out in the experimental garden of the Faculty of Agriculture, Muhammadiyah University, West Sumatra, Tanjung Gadang sub-district, West Payakumbuh sub-district, Payakumbuh City at an altitude location ± 514 meters from sea level, soil type Inseptisol. Implementation of this field trial will start from August 2022 to November 2022. The design used in the experiment was a Completely Randomized Design (CRD) with 5 treatments and 4 replications so that there were 20 replications in total, in each replication there were 4 polybags of pepper plants, 2 of which were used as sample plants so that the total number of plants was 80 polybags. Each polybag contains 1 plant. Observations were carried out at 4 weeks after planting at intervals of once a week. The results of the observation data were averaged and analyzed statistically using the F test at a significance level of 5%. The treatments given were as follows: 0 ml POC banana weevil/planting, 20 ml POC banana weevil/planting, 40 ml POC banana weevil/planting, 60 ml POC banana weevil/planting and 80 ml POC banana weevil/planting. The observation parameters carried out on pepper seedlings were when shoots appeared, plant height, number of leaves, stem diameter, longest leaf length, widest leaf width, primary root length, plant wet weight and plant dry weight. From the experimental results, it can be concluded that administering liquid organic fertilizer (POC) at a dose of 60 ml/plant and a dose of 80 ml/plant provides the best response to the growth of pepper plant seeds.